Coconut pith as partially replacement in sand brick - Yahya, Nur Faezah; Abd Aziz, Nur Liyana; Osman, Mohamad Hairi; Tuan Ismail, Tuan Noor Hasanah; Adnan, Suraya Hani; A Rahman, Noor Khazanah; Abd Rashid, Razlin (Penerbit UTHM, 2020)
Recently, the demand for the brick production has been increase because of the increasing development of construction project in Malaysia. Brick can be categorized in few type such as clay brick, sand brick, sand lime brick and concrete brick. Sand brick is commonly used in low and high medium cost housing development and other commercial construction in Malaysia. In order to increase the quality value of brick and to set forth in produce the sustainable product, many effort and alternatives has been conducted which is to reuse the waste material in brick production. The coconut pith used in production of sand brick as a partially replacement material to reduce the usage of sand in order to determine the characteristic of coconut pith in sand brick. In the production of sand brick, the percentage of coconut pith that were used in this study is 0%, 0.5%, 1.0% and 1.5% and the mix for the mixture of brick is according to ratio standard which is 1:6. Then, the size of sample is 215mm × 102.5mm × 65mm and testing were conducted for production of sand brick are compressive strength, water absorption and density test according to standard MS 76:1972. Through this studies 0.5% of coconut pith is the suitable percentage in sand brick with the compression strength value is 7.63 N/mm², 16.76% of water absorption and 1971.27 kg/mm³ as density value when compare the Malaysian standard and Blacktop Industries. The usage on coconut pith can be used as an alternative in order to reduce the pollution environment and reduce the waste material.